Sweaty Archives – Training the Writing of Bodies in Virtual Spaces (Urdimento - Revista de Estudos em Artes Cênicas, 2025)
This article explores the concept of the body-as-archive in the context of extended realities (XR). Drawing on a feminist and decolonial epistemological framework, we aim to weave a research methodology for analyzing the rewriting of psychophysical training practices for performers, focusing on the work of actresses Iben Nagel Rasmussen and Roberta Carreri from Odin Teatret (DK) and LUME Teatro (BR). By integrating immersive technologies, we propose new methods for preserving and transforming this form of intangible cultural heritage, addressing challenges in documenting embodied knowledge and promoting intersectional dialogues between culture, body, and technology.